An exploration of the relationships between student racial background and the school sub-contexts of office discipline referrals: a critical race theory analysis. Issue 3 (4th May 2018) - Anyon, Yolanda; Lechuga, Chalane; Ortega, Debora; Downing, Barbara; Greer, Eldridge; Simmons, John
Abstract: A growing body of research indicates that exclusionary school discipline practices disproportionately impact students of color. Some scholars have theorized that racial disparities likely vary across school sub-contexts, as implicit bias in perceptions of student behavior may be more influential in locations where students and adults have weaker relationships (e.g. bathrooms and hallways, compared to the classroom). Guided by Critical Race Theory, this study used administrative data from a large urban school district ( n = 20, 166 discipline incidents, 9, 170 students, and 185 schools) to consider the relationship between student race and the locations where youth are disciplined. Results indicate that Black, Latino/a, and Multiracial youth were no more likely than White students to have a discipline incident take place outside the classroom. These findings suggest attention is needed to the role of systemic bias and colorblind policies and practices in discipline disparities.